2018
DOI: 10.5194/acp-18-17819-2018
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis of summertime ground site measurements in the Athabasca oil sands with a focus on analytically unresolved intermediate-volatility organic compounds

Abstract: Abstract. In this paper, measurements of air pollutants made at a ground site near Fort McKay in the Athabasca oil sands region as part of a multi-platform campaign in the summer of 2013 are presented. The observations included measurements of selected volatile organic compounds (VOCs) by a gas chromatograph–ion trap mass spectrometer (GC-ITMS). This instrument observed a large, analytically unresolved hydrocarbon peak (with a retention index between 1100 and 1700) associated with intermediate-volatility organ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 96 publications
3
29
0
Order By: Relevance
“…For some samples with high volatilities (e.g., naphtha and n-heptane), the gas phase was further diluted before being injected into the reactor. The total hydrocarbon (THC) concentration entering the ECCC-OFR was determined by passing the input gas stream (in offline experiments) through a Pt-based catalytic converter maintained at 400 • C and measuring the subsequently evolved CO 2 (LI-COR LI-840A) as described by Veres et al (2010). The evolved CO 2 concentration (ppb) is converted to the total carbon concentration (ppbC; see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some samples with high volatilities (e.g., naphtha and n-heptane), the gas phase was further diluted before being injected into the reactor. The total hydrocarbon (THC) concentration entering the ECCC-OFR was determined by passing the input gas stream (in offline experiments) through a Pt-based catalytic converter maintained at 400 • C and measuring the subsequently evolved CO 2 (LI-COR LI-840A) as described by Veres et al (2010). The evolved CO 2 concentration (ppb) is converted to the total carbon concentration (ppbC; see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…S7 and Fig. S2) but has been shown to be equally efficient at lower carbon numbers (Veres et al, 2010). The THC concentration was measured before and after each experiment, resulting in differences of less than 5 %.…”
Section: Methodsmentioning
confidence: 99%
“…The absolute value of the O 4 cross section and its dependence on temperature is uncertain. Some studies suggest that the absolute value of the cross section may be overestimated by up to 25 %, requiring the use of a scaling factor (Clémer et al, 2010;Wagner et al, 2002Wagner et al, , 2009Wagner et al, , 2019. However, Frieß et al (2011) found that the best results for measured O 4 dSCDs and the vertical profiles of aerosol extinction retrieved from them were achieved without a scaling factor.…”
Section: Max-doas Fittingmentioning
confidence: 99%
“…The laser-off and laser-on modes of SP-AMS measurements were used for quantifying the non-refractory particulate matter (NR-PM; including SO 2− 4 , NO − 3 , NH + 4 and organics) and refractory black carbon (rBC), respectively (A. K. Y. Onasch et al, 2012), and for performing source-apportionment analysis of ambient organic aerosol via positive matrix factorization (PMF; Ulbrich et al, 2009;Zhang et al, 2011). Single-particle characterization was achieved from 22 to 29 August 2013 by deploying another co-located SP-AMS equipped with a lightscattering module (A. K. Y. in order to assess the mixing state of the NR-PM during the ground-based campaign.…”
Section: Introductionmentioning
confidence: 99%